PARIWISATA PEDESAAN SEBAGAI PAKET WISATA ALTERNATIF: KASUS DESA WISATA TAMAN SLAU - Wirata, I Nengah (JURNAL KEPARIWISATAAN, 2010)
This study aims to identify the activities of the tourists taking part in trekking package tour in Undisan Village, Bangli, organized by PT.Suartur and to find out how members of the community participate in it. Data were collected by participate,y observation, and structured interview. The key informants are the formal and informal community leaders, some local people, managerial staff of PT. Suartur, officers of Bangli Tourism Department, and some tourists who experience the trekking package. Descriptive-qualitative research design and the theory of structural functionalism and sustainable community-based tourism development are used in this study. The result shows that tourist activities during the trekking package tour is to enjoy the panorama of the countryside that is still natural with its fresh and unpolluted air and to observe the daily socio-economic and socio-cu_ltural life of the community. The tourists are satisfied with this trekking package because they can interact with the members of the community and are particularly interested in the cultural elements found along the trekking path. They wish to visit the Village again in the future. Participation of the members of the community is still limited.